1990
DOI: 10.1093/oxfordjournals.humrep.a137111
|View full text |Cite
|
Sign up to set email alerts
|

The effect of RU 486 administered during the early luteal phase on bleeding pattern, hormonal parameters and endometrium

Abstract: The purpose of the present study was to investigate the effect of a single dose of RU 486 administered very early in the secretory phase on endometrial development and levels of progesterone receptors, on plasma levels of gonadotrophins and ovarian hormones and on the pattern of menstrual bleeding. Twenty-four regularly menstruating subjects participated and were studied during a control, a treatment and a follow-up cycle. In the treatment cycle, a single dose of 200 mg RU 486 was given in the evening of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(36 citation statements)
references
References 11 publications
3
32
0
1
Order By: Relevance
“…All P 4 serum levels obtained on LHC7 were within expected values for a spontaneous normal menstrual cycle (O30 nmol/l) with no statistically significant differences between the mifepristone-and placebotreated groups (Table 1) in agreement with previous reports (Swahn et al 1990). No unscheduled bleeding or spotting was reported.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…All P 4 serum levels obtained on LHC7 were within expected values for a spontaneous normal menstrual cycle (O30 nmol/l) with no statistically significant differences between the mifepristone-and placebotreated groups (Table 1) in agreement with previous reports (Swahn et al 1990). No unscheduled bleeding or spotting was reported.…”
Section: Resultssupporting
confidence: 89%
“…After 5 days of mifepristone administration is difficult to speculate about the proportion of PGRs that remain blocked in the endometrium since to our knowledge there is no report regarding this matter so far. The studies performed with mifepristone administration during the early luteal phase showed an out-of-phase endometrial development in spite of high circulating P 4 , suggesting a persistent block of the PGR (Swahn et al 1990). The administration of mifepristone (200 mg) in LHC2 reaches a peak circulating level of w0.3-0.4 mmol/l within 2 h (Sarkar 2002) and is able to alter uterine gene expression in early pregnancy as early as 6 h after oral administration (Critchley et al 1996).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other study also reported a higher pregnancy rate in Cassia twig Tuckahoe capsule group, 5 out of 10 endometriosis patients with infertility were pregnant in comparison to mifepristone [26]. Mifepristone decreases estrogen, progesterone, luteinizing hormone and makes endometrial incapable for implantation which is against pregnancy [27] [28] [29].…”
Section: Discussionmentioning
confidence: 99%